Linopirdine blocks α9α10-containing nicotinic cholinergic receptors of cochlear hair cells - Gomez-Casati, M.E. (2004)
Studies of the electrophysiological response to acetylcholine (ACh) in mammalian outer hair cells (OHCs) are hindered by the presence of a large potassium current, IK,n, most likely mediated by channels containing the KCNQ4 subunit. Since IK,n can be blocked by linopirdine, cholinergic effects might be better revealed in the presence of this compound. The aim of the present work was to study the effects of linopirdine on the ACh-evoked responses through α9α10-containing native and recombinant nicotinic cholinergic receptors. Responses to ACh were blocked by linopirdine in both OHCs and inner hair cells (IHCs) of rats at postnatal days 21-27 (OHCs) and 9-11 (IHCs). In addition, linopirdine blocked responses of recombinant α9α10 nicotinic cholinergic receptors (nAChRs) in a concentration-dependent manner with an IC50 of 5.2 μM. Block by linopirdine was readily reversible, voltage independent, and surmountable at high concentrations of ACh, thus suggestive of a competitive type of interaction with the receptor. The present results contribute to the pharmacological characterization of α9α10-containing nicotinic receptors and indicate that linopirdine should be used with caution when analyzing the cholinergic sensitivity of cochlear hair cells.